Do local and expatriate managers motivate the local workforce differently? a cultural perspective. - Ng, Siow Leng. (2008)
Competition for the “best people” has never been easy for organizations. In tough conditions like a shrinking labor pool, looking towards foreign shores might seem a likely answer. In these circumstances, sensitivity to different cultures needs to be heightened in order to motivate and promote teamwork. In short, effective employee motivation hinges on both cultural harmony and a good understanding of what makes an employee satisfied.